2022
DOI: 10.3389/fimmu.2022.974581
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the immune microenvironment and their clinical significance in non-small cell lung cancer patients with ALK-rearranged mutation

Abstract: BackgroundAlthough immune checkpoint inhibitors (ICIs) are one of the most important treatments for advanced-stage non-small-cell lung cancer (NSCLC), NSCLC patients with ALK-rearranged usually don’t obtain a clinical benefit. The reason may be related to the unique tumor microenvironment (TME). We evaluated the characteristics of immune biomarkers of the TME and their prognostic value in ALK-rearranged NSCLC.MethodsTumor samples from patients with ALK-rearranged (N = 39) and EGFR- (N = 40)/KRAS- (N = 30) muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…However, this difference in T reg cells was not seen by IHC in a cohort of 39 patients with ALK+ NSCLC ( 70 ). Within the cohort of 39 patients with ALK+ NSCLC, CD8 + T cell expression of checkpoints PD-1, CTLA-4, lymphocyte activating gene 3 (Lag3), T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3) by IHC was markedly reduced ( 70 ). This suggests infiltrating CD8 + T cells were unable to engage with potential tumor antigens as T cell checkpoint expression is upregulated by T cell activation ( 72 ).…”
Section: The Alk+ Nsclc Interface With the Immune Systemmentioning
confidence: 96%
See 3 more Smart Citations
“…However, this difference in T reg cells was not seen by IHC in a cohort of 39 patients with ALK+ NSCLC ( 70 ). Within the cohort of 39 patients with ALK+ NSCLC, CD8 + T cell expression of checkpoints PD-1, CTLA-4, lymphocyte activating gene 3 (Lag3), T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3) by IHC was markedly reduced ( 70 ). This suggests infiltrating CD8 + T cells were unable to engage with potential tumor antigens as T cell checkpoint expression is upregulated by T cell activation ( 72 ).…”
Section: The Alk+ Nsclc Interface With the Immune Systemmentioning
confidence: 96%
“…Comparative mRNA studies of 31 samples from ALK+ NSCLC patients who were treatment naïve found an increase in T regulatory (T reg ) cells within the ALK+ NSCLC TME compared to patients with EGFR+ NSCLC or patients with ALK− and EGFR− NSCLC (71). However, this difference in T reg cells was not seen by IHC in a cohort of 39 patients with ALK+ NSCLC (70). Within the cohort of 39 patients with ALK+ NSCLC, CD8 + T cell expression of checkpoints PD-1, CTLA-4, lymphocyte activating gene 3 (Lag3), T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3) by IHC was markedly reduced (70).…”
Section: The Alk+ Nsclc Tmementioning
confidence: 98%
See 2 more Smart Citations
“…The tumor microenvironment of ALK-positive NSCLC has been demonstrated to be immunosuppressive ( 13 ). It has been reported that Crizotinib can stimulate immunogenic cell death ( 14 , 15 ), which might mediate the induction of potent anti-tumor immune responses.…”
Section: Introductionmentioning
confidence: 99%